Gazette of 30% indigenous entitlement in every government’s tender the case study of Seri Gelam Enterprise / Harnizah Hajar - Hajar, Harnizah (Faculty of Business and Management, 2011)
Indigenous company that involving in the hardware and building material industry now is increasingly. As time goes by, the indigenous company tries to compete with other races that involve in the same industry. Chinese company is the first ranking that is as a competitor for them, from the materials that they sell to the tender that they grabbed. In Social Contract of Malaysia, indigenous has their power of entitlement to be that can help them by Government’s supports and this can improve their performances in the future. In the case of Seri Gelam Enterprise Sdn bhd, this company is actually one of the indigenous companies that success in their business for almost 18 years. However, the 30 percent indigenous entitlement in every government’s tender will help them to improve their performances as well as put the best strategies that can increase their profit in the future. This study consists of four chapters. Chapter 1 explains the background and introduction of the study while Chapter 2 is on issue arise from the study as well as its purpose. Chapter 3 explores literatures related to the title and Chapter 4 discuss on the findings obtained to support the issue. Finally conclusion is summarized on the last topics. Based on the findings, the indigenous company still hopes for the indigenous entitlement as they want their rights, to compete with the other company that well established and being manipulated by the Chinese is not easy for the indigenous company to compete with them. It is risky and this creates the company in debts and then bankrupted.